DIGITAL TRANSFORMATION OF EDUCATION: INTERNATIONAL, EUROPEAN & NATIONAL REFORM FRAMEWORKS FOR REBUILDING SECONDARY EDUCATION IN UKRAINE - Olesya Stoyka (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This article aims to analyse the multi-level policy architecture guiding the digital transformation of general secondary education in Ukraine as a strategic mechanism for educational reconstruction in the context of war-related disruption. The research employs a qualitative comparative policy analysis methodology, examining international (UNESCO, OECD, World Bank), European (EU Digital Education Action Plan 2021–2027, DigComp, DigCompEdu), and national reform frameworks (New Ukrainian School, National Recovery Plan, Digital Agenda Ukraine 2030). The methodological approach also integrates comparative case analysis of post-crisis digital education reforms in selected European countries. The findings reveal substantial convergence between European and Ukrainian digital education strategies, particularly in teacher competence development, curriculum modernisation, and governance alignment. However, critical implementation gaps persist in digital infrastructure, connectivity equity, and national learning data governance. The study also identifies five strategic pillars—digital infrastructure, teacher competence, curriculum integration, learning analytics, and policy coherence—as essential foundations for systemic transformation. The conclusions emphasise that digital transformation should be understood not merely as technological modernisation but as a comprehensive reform framework essential for rebuilding a resilient, equitable, and future-ready secondary education system in Ukraine. Sustained multi-level governance coordination, targeted investment, and alignment with European digital competence frameworks are identified as decisive conditions for successful long-term educational recovery.